Weekly High Dose Versus Daily Low Dose Vitamin D3 in Treatment of Vitamin D3 Deficiency in Pregnancy: A Randomized Controlled Clinical Trial - Rostami, Farahnaz (J Family Reprod Health, 2018)
Objective: To compare administration of weekly high dose versus daily low dose vitamin D(3) in treatment of vitamin D(3) deficiency in pregnancy. Materials and methods: A randomized controlled clinical trial was performed between July 2016 until 2 July 2017 on 215 pregnant women with vitamin D(3) deficiency (serum levels < 30 ng/ml) and gestational age less than 14 weeks. The participants were randomly assigned to 2 treatment groups of A: receiving 1000 unit vitamin D(3) daily, and B: 50,000 units weekly for 10 weeks. At 24-28 weeks of gestation, serum levels of vitamin D(3) were measured again. Data entry and statistical analysis were performed by SPSS software v. 20 and P value less than 0.05 was considered as statistically significant level. Results: Primary mean serum vitamin D3 level in group A was: 17.3 ± 6.8 and in group B: 15.2 ± 7.3 ng/ml while mean serum vitamin D3 level after treatment in group A was significantly lower than group B (31.9 ± 118 B vs. 42.9 ± 15.5, p-value: < 0.001); both groups were successfully treated, no remarkable side effects were observed in either groups. Conclusion: As both regimens treat vitamin D deficiency successfully and consuming weekly high dose vitamin D(3) makes more acceptable serum levels for mothers with no apparent side effects weekly high dose vitamin D(3 )can be safely administered for vitamin D(3) deficiency in pregnancy, if further studies show similar results.